"The Interpretation of the Bible in the Church" and Interpretation in the Biblical Tradition - Beckman, Peter (Theoforum, 2020)
The Pontifical Biblical Commission's document The Interpretation of the Bible in the Church (IBC) details interpretive methods which the Roman Catholic exegete should use in the study of Biblical texts. Scripture itself is a living tradition of interpretation as later texts re-read and re-apply earlier passages to their current situations. The IBC stresses the aspect of "Re-Readings" and the "Relationship between the Old Testament and the New". This article will highlight the IBC's description of these processes, then further survey these interpretive actions, and finally assess the tension in their usage.